2016
DOI: 10.1038/srep39096
|View full text |Cite
|
Sign up to set email alerts
|

Human dental stem cells suppress PMN activity after infection with the periodontopathogens Prevotella intermedia and Tannerella forsythia

Abstract: Periodontitis is characterized by inflammation associated with the colonization of different oral pathogens. We here aimed to investigate how bacteria and host cells shape their environment in order to limit inflammation and tissue damage in the presence of the pathogen. Human dental follicle stem cells (hDFSCs) were co-cultured with gram-negative P. intermedia and T. forsythia and were quantified for adherence and internalization as well as migration and interleukin secretion. To delineate hDFSC-specific effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 59 publications
3
18
0
1
Order By: Relevance
“…However, this was only obtained from a single cell line. Although Ca9-22 has been employed in many periodontal studies (47)(48)(49), it is important to confirm what we found in this study in other gingival epithelial cells to clarify the physiological relevance of our findings.…”
Section: Discussionsupporting
confidence: 74%
“…However, this was only obtained from a single cell line. Although Ca9-22 has been employed in many periodontal studies (47)(48)(49), it is important to confirm what we found in this study in other gingival epithelial cells to clarify the physiological relevance of our findings.…”
Section: Discussionsupporting
confidence: 74%
“…Thereafter, additional studies revealed that human dental follicle stem cells (hDFSCs) elicit a reduced pro-inflammatory response following bacterial infection, as compared to differentiated cells ( Biedermann et al, 2014 ). Furthermore, Kriebel et al (2013) and Biedermann et al (2014) showed that stem cell functions were influenced by oral bacteria in vitro , while Hieke et al (2016) found that infection with viable bacteria induced distinct reactions by stem cells that were different from reactions to a single administration of LPS ( Hieke et al, 2016 ). Thus, infected stem cells showed a reduced capacity for migration, though that finding is inconsistent with another study that demonstrated increased migration following stimulation with LPS ( Chatzivasileiou et al, 2013 ).…”
Section: Host–pathogen Interaction and Molecular Effects On Host Cellmentioning
confidence: 99%
“…The effect of PDLSCs on neutrophils seems to be independent on cell-to-cell contact. Human DFSCs infected with periodontal pathogens P. intermedia or T. forsythia reduce neutrophil chemotaxis, phagocytic activity and NET formation [151]. Further investigations are needed to clarify the interactions between MSCs of dental origin and polymorphonuclear neutrophils as well as their underlying mechanisms.…”
Section: Polymorphonuclear Neutrophilsmentioning
confidence: 99%